MODOS DE PARTICIPAR: INTERFERÊNCIAS E IRREVERÊNCIAS ESTUDANTIS NO IFES - CAMPUS SERRA - Quinino, Cynthia Kruger (2020)
This paper aimed at following students ways of participation as well as their interferences on formation and management processes at Ifes - Campus Serra. The campus offers professional and technological education in a city built up in the midst of many p